Influence of low dose of gamma radiation and storage on some vitamins and mineral elements of dried oyster mushrooms (Pleurotus ostreatus) - Kortei, N.K.; Odamtten, G.T.; Obodai, M.; Wiafe-Kwagyan, M.; Addo, E.A. (Food Science and Nutrition, 2017)
Mushrooms contain some of the most potent natural medicines on the planet. Vitamins A, C, D, Mineral elements, contents, as well as total soluble solids (Brix o ) of dried composition of Pleurotus ostreatus were investigated after exposing to gamma radiation doses of 0 (control), 0.5, 1, 1.5, and 2 kGy at a dose rate of 1.7 kGy per hour in air from a Cobalt 60 source (SLL 515, Hungary) batch irradiator prior to storage (0 month) and after storage (12 months) at room temperature (28 ± 2°C). Results obtained showed some significant (p <.05) differences due to irradiation and storage. Before storage, vitamins A, C, and D contents of dried and irradiated mushrooms ranged 0.003 ± 0.08–0.014 ± 0.08, 0.042 ± 1.06–0.132 ± 1.06, and 0.040 ± 0.76–0.057 ± 0.76 mg/g, respectively. After 12 months, vitamin contents decreased and ranged 0.0029 ± 0.08–0.010 ± 0.08, 0.038 ± 1.06–0.125 ± 1.06, and 0.031 ± 0.76–0.05 ± 0.76 mg/g for vitamins A, C, and D, respectively. Total soluble solids recorded 1.5 Brix o , however, showed no significant difference (p >.05) and did not change in 12 months after gamma irradiation up to 2 kGy. Sodium ranged from 14.00 ± 0.7 to 14.90 ± 0.8 mg/100 g. Potassium content varied from 30.20 ± 0.5 to 33.10 ± 0.6 mg/100 g. Magnesium content ranged 1.27 ± 0.15–3.53 ± 0.04 mg/100 g. Calcium ranged 11.00 ± 0.4–12.53 ± 0.4 ± 0.03 mg/100 g. Phosphorus content ranged 6.11 ± 0.30–6.41 ± 0.35 mg/100 g, whereas Nitrogen content was found to be 3.00 ± 0.03–3.60 ± 0.25 mg/100 g. Microelements or heavy metals included Copper; detected ranged 0.00 ± 0.00–0.02 ± 0.001 mg/100 g, Zinc content ranged 0.01 ± 0.002–0.03 ± 0.001 mg/100 g. Iron content was found to be in the range 0.29 ± 0.01–0.37 ± 0.1 mg/100 g. Manganese content was found to be in the range 0.03 ± 0.001–0.04 ± 0.01 mg/100 g. Lead content was found to be 0.00 ± 0.00–0.03 ± 0.001 mg/100 g. Food processing and storage has the potential to slightly alter the stability of vitamins in foods. Pleurotus ostreatus showed appreciable levels of mineral elemental composition, essential vitamins A, C, and D, and can be endorsed as a natural medicinal food product in the food and pharmaceutical industries. The heavy metals detected were with also below the upper limits permissible by the WHO standards and is thus safe for human consumption. © 2016 The Authors. Food Science & Nutrition published by Wiley Periodicals, Inc.
Keywords: gamma irradiation; mineral elements; oyster mushrooms; P. ostreatus; storage; total soluble solids; vitamins